Methodological development of a specific tool for assessing acceptability of assistive systems of powered two‐wheeler‐riders. Issue 1 (1st February 2015) - Füssl, Elisabeth; Oberlader, Manuel; Beanland, Vanessa; Spyropoulou, Ioanna; Lenné, Michael G.; Joshi, Somya; Rößger, Lars; Leden, Lars; Underwood, Geoff; Carvalhais, Jose
Abstract : Research on the acceptability of assistive systems for improving the safety of powered two‐wheelers (PTWs) is a pressing issue. The use of safety‐enhancing assistive systems for motorised vehicles, including advanced driver assistance systems and in‐vehicle information systems is widespread in many countries. Yet, there is only a limited number of equivalent intelligent transport systems (ITS) for PTWs, namely advanced rider assistance systems and on‐bike information systems. This study describes the methodological development of a specific tool for assessing motorcyclists' acceptability of ITS, as part of the motorcyclists' profiling questionnaire (MOPROQ). There were three stages of development. First, a literature review was undertaken to assess the current state of the art regarding ITS for PTWs and to determine the most relevant facets of acceptability that should be measured. Second, a series of focus group interviews were conducted to explore riders' attitudes towards ITS. Finally, the focus group results were used to develop a large‐scale survey (MOPROQ), which was administered to an initial sample of over 6000 riders internationally. The designed tool can be used as a basis for the determination of rider acceptability of ITS systems in the future.